Assessing the sustainability of pension reforms in Europe: a pension wealth approach - Grech, Aaron George (Munich, 2014)
"In this lecture, I will try to start answering the question of whether the pension reforms enacted in Europe since the 1990s will prove to be sustainable. This broad question has embedded in it both theoretical and empirical sub-questions. On the theoretical side, I will need to see how best to measure pension adequacy, while also assessing the feasibility of evaluating jointly pension adequacy and financial sustainability. Once this is tackled, I will be assessing the possible impact of reforms on the capacity of pension systems to achieve their goals and the impact on the constraints they face. This should help understand better any sources of possible pressures that could undermine the sustainability of pension reforms."